Chaos created by CHAOS!! : A Case Report - Roy, Deepa Durga; Nigam, Manish; Taori , Abhijeet; Taori , Abhijeet (Journal of Indian Academy of Forensic Medicine, 2014)
A 22 years old unbooked primigravida with 18 weeks amenorrhea came to the department of obstetrics and gynecology at Sri Aurobindo hospital for a routine checkup. On her sonography, the fetus was found to have multiple congenital malformations. The post abortus fetus, on autopsy, turned out to be one of the extremely rare cases of CHAOS. CHAOS (Congenital High Airway obstruction Syndrome) is a rare and commonly fatal abnormality pertaining to innate obstruction of the fetal airway. Most authors postulate that this malformation is related to a cessation of the embryological development of the Sixth brachial arch at different gestational junctures. In our case of CHAOS, a confirmation of the preliminary diagnosis, with location of the precise site, level and degree of obstruction was attained with the help of an autopsy. Foetal autopsies should be encouraged as they symbiotically benefit the parents and the clinicians to a more clear and precise diagnosis.